Women in the two Germanies : a comparative study of a socialist and a non-socialist society - Shaffer, Harry G. (Pergamon policy studies on social issues., 1981)
Women in the Two Germanies: A Comparative Study of a Socialist and a Non-Socialist Society is a comparative study of the status and position of women in socialist East Germany and non-socialist West Germany. Drawing on research carried out in 1977 and 1978, as well as interviews with hundreds, if not thousands, of individuals from all walks of life and from all parts of the two Germanies, this book considers a wide variety of legal, economic, political, and social aspects of life in the two countries, such as equality or the lack thereof under the law, in education, on the job, and in the home.